First continuous pre-Jaramillo to Jaramillo terrestrial vertebrate succession from Europe - Piñero García, Pedro (2020)
In this paper, the early Pleistocene small vertebrate sequence of Quibas-Sima (Quibas karstic complex, Murcia, SE Spain) is presented. The available magnetostratigraphic information together with the small vertebrate association, allow to reliably constrain the age of the different units. The basal unit of the section has recorded a reversed polarity assigned to the pre-Jaramillo Matuyama (C1r.2r, i.e., between 1.2 and 1.07 Ma). The intermediate units have recorded a normal polarity correlated directly with the Jaramillo subchron (C1r.1n, between 1.07 and 0.99 Ma), while the upper units record the post-Jaramillo reverse polarity (C1r.1r, i.e., between 0.99 and 0.78). Jaramillo subchron is especially significant regarding the earliest hominin dispersal in Western Europe. However, vertebrate faunas unambiguously correlatable with Jaramillo subchron are extremely rare in Europe. Thereby, the study of the Quibas-Sima sequence allows to characterize the vertebrate association synchronous to this paleomagnetic episode in southern Iberian Peninsula, and contributes to increase knowledge of the biotic and climatic events that took place in southern Europe at the beginning of the Early-Middle Pleistocene transition, prior to the Matuyama-Brunhes boundary. A continuous small vertebrate succession has been reported, including representatives of the families Bufonidae, Pelodytidae, Testudinidae, Gekkonidae, Blanidae, Lacertidae, Colubridae, Viperidae, Soricidae, Erinaceidae, Rhinolophidae, Vespertilionidae, Muridae, Gliridae, Sciuridae, Leporidae and Ochotonidae The ecological affinities of the faunal association suggest a progressive reduction in forest cover in the onset of the Jaramillo subchron.